Associations and effects of omega-3 polyunsaturated fatty acids on cognitive function and mood in healthy adults: a protocol for a systematic review of observational and interventional studies. Issue 6 (22nd June 2019) - O' Donovan, Fiona; Carney, Síle; Kennedy, Jean; Hayes, Heather; Pender, Niall; Boland, Fiona; Stanton, Alice
Abstract : Introduction: The association between long-chain omega-3 polyunsaturated fatty acids (PUFAs), brain health, cognitive function and mood has been the subject of intensive research. Marine-derived omega-3 PUFAs, such as docosahexaenoic acid and eicosapentaenoic acid, are highly concentrated in neuronal membranes and affect brain function. Many studies have found that consumption of omega-3 PUFAs is associated with lower risk of cognitive or mood dysfunction. However, other studies have demonstrated no beneficial effects. There appears to be inconsistent findings from both epidemiological and randomised controlled trial (RCT) studies. The aim of this review is to compile the previous literature and establish the efficacy of omega-3 PUFAs in enhancing cognitive performance and mood in healthy adults. Methods and analysis: Prospective cohort studies, RCTs, controlled clinical trials, controlled before and after studies, interrupted time series with a minimum of 3 months duration will be eligible for inclusion. Studies on healthy adults over the age of 18, where the intervention/exposure of interest is omega-3 PUFAs will be included. The outcomes of interest are cognition and mood. Studies will be eligible for inclusion if they measure changes in cognitive function or mood, or the risk of developing cognitive or mood disorders using validated tools and assessments. Relevant search terms and keywords will be used to generate a systematic search in Cochrane Library, MEDLINE, EMBASE, PsycINFO, Cumulative Index to Nursing and Allied Health Literature, Web of Science, Scopus and the grey literature. Two independent reviewers will screen studies for eligibility. Risk of bias in cohort and non-randomised studies will be assessed using the ROBINS-I tool. The Cochrane Collaboration's tool for assessing risk of bias in randomised trials will be used for RCTs. If there are sufficient data, a meta-analysis will be conducted. Ethics and dissemination: This systematic review does not involve primary data collection and therefore formal ethical approval is not required. Results will be disseminated through peer reviewed publications, conference presentations and the popular press. PROSPERO registration number: CRD42018080800.